Ethynyl‐Tolyl Extended 2‐(2′‐Hydroxyphenyl)benzoxazole Dyes: Solution and Solid‐state Excited‐State Intramolecular Proton Transfer (ESIPT) Emitters. Issue 5 (4th December 2018) - Munch, Maxime; Curtil, Mathieu; Vérité, Pauline M.; Jacquemin, Denis; Massue, Julien; Ulrich, Gilles
Abstract : Dual solution/solid‐state emissive fluorophores based on a 2‐(2′‐Hydroxyphenyl)benzoxazole (HBO) core bearing one or two ethynyl‐tolyl moieties at different positions were synthesized via an expedite two‐step synthetic procedure. HBO derivatives are known to display intense Excited‐State Intramolecular Proton Transfer (ESIPT) emission in the solid‐state but are mildly emissive in solution due to the detrimental flexibility of the excited‐state opening efficient non‐radiative pathways. The sole introduction of a rigid ethynyl moiety led to a sizeable enhancement of the fluorescence quantum yield in solution, up to a 15‐fold increase in toluene as compared to unsubstituted HBO dyes while keeping the high solid‐state fluorescence efficiency. The position of the substitution on the π‐conjugated core led to subtle fine‐tuning of maximum emission wavelengths and quantum yields. Moreover, we show that the ethynyl tolyl substituent at the para position of the phenol ring is a suitable moiety for an efficient stabilization of the corresponding emissive anionic HBO derivatives in dissociative solvents like DMF THF or EtOH. These observations were confirmed in CH3 CN by a basic titration. For all dyes, the nature of the excited‐state involved in the fluorescence emission was rationalized using ab initio calculations. Abstract : A series of ESIPT emitters based on ethynyl‐extended HBO scaffolds has been synthesized. Their optical properties reveal increased quantum yields values in solution as compared to unsubstituted analogues while keeping strong fluorescence intensities in the solid‐state. These scaffolds also allow the stabilization of an anionic species in selected cases, as evidenced by basic titrations. The nature of the excited‐states was also rationalized using ab initio calculations.